Different combinations of monensin and narasin on growth performance, carcass traits, and ruminal fermentation characteristics of finishing beef cattle - Baggio, Marcelo; Gouvêa, Vinícius N.; Barroso, José Paulo R.; Miszura, Alexandre A.; Limede, Arnaldo C.; Soares, Letícia C. B.; Ferraz, Marcos Vinicius C.; Vicente, Ana Carolina S.; Ferreira, Evandro M.; Marques, Rodrigo S.; Pires, Alexandre V. (Frontiers in Veterinary Science, 2023)
The objective of this study was to evaluate the effects of different combinations of monensin and narasin on finishing cattle. In Exp. 1, 40 rumen-cannulated Nellore steers [initial body weight (BW) = 231 ± 3.64 kg] were blocked by initial BW and assigned to one of the five treatments as follows: Control (CON): no feed additive in the basal diet during the entire feeding period; Sodium monensin (MM) at 25 mg/kg dry matter (DM) during the entire feeding period [adaptation (days 1–21) and finishing (days 22–42) periods]; Narasin (NN) at 13 mg/kg DM during the entire feeding period (adaptation and finishing periods); Sodium monensin at 25 mg/kg DM during the adaptation period and narasin at 13 mg/kg DM during the finishing period (MN); and narasin at 13 mg/kg DM during the adaptation period and sodium monensin at 25 mg/kg DM during the finishing period (NM). Steers fed MM had lower dry matter intake (DMI) during the adaptation period compared to NM (P = 0.02) but not compared to CON, MM, MN, or NN (P ≥ 0.12). No differences in DMI were observed among the treatments during the finishing (P = 0.45) or the total feeding period (P = 0.15). Treatments did not affect the nutrient intake (P ≥ 0.51) or the total apparent digestibility of nutrients (P ≥ 0.22). In Exp. 2, 120 Nellore bulls (initial BW = 425 ± 5.4 kg) were used to evaluate the effects of the same treatments of Exp. 1 on growth performance and carcass characteristics of finishing feedlot cattle. Steers fed NM had greater DMI during the adaptation period compared to CON, MM, and MN (P ≤ 0.03), but no differences were observed between NM and NN (P = 0.66) or between CON, MM, and NN (P ≥ 0.11). No other differences between treatments were observed (P ≥ 12). Feeding narasin at 13 mg/kg DM during the adaptation period increases the DMI compared to monensin at 25 mg/kg DM, but the feed additives evaluated herein did not affect the total tract apparent digestibility of nutrients, growth performance, or carcass characteristics of finishing cattle.